2004
DOI: 10.1128/jb.186.9.2603-2611.2004
|View full text |Cite
|
Sign up to set email alerts
|

HybF, a Zinc-Containing Protein Involved in NiFe Hydrogenase Maturation

Abstract: HypA and HypB are maturation proteins required for incorporation of nickel into the hydrogenase large subunit. To examine the functions of these proteins in nickel insertion, the hybF gene, which is a homolog of hypA essential for maturation of hydrogenases 1 and 2 from Escherichia coli, was overexpressed, and the product was purified. This protein behaves like a monomer in gel filtration and contains stoichiometric amounts of zinc but insignificant or undetectable amounts of nickel and iron. In filter binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
99
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 60 publications
6
99
1
Order By: Relevance
“…HypA (also known as HybF) is a Zn-containing protein (Atanassova and Zamble 2005)) but also binds stoichiometric amounts of nickel, and HypB is a GTPase (Blokesch et al 2004a;Leach et al 2005). The present model is that HypA serves as a nickel chaperone, and HypB as a regulator that thermodynamically controls the donation of the metal to the hydrogenase apoprotein or release of the nickel-free chaperone (Blokesch et al 2004c;Leach et al 2005;Reissmann et al 2003). The present model for HypA/HypB function (Leach et al 2005) involves a key metal binding site in HypB beyond the usual (Ni-binding) polyhistidine stretch.…”
Section: Accessory Proteins For Hydrogenase Maturationmentioning
confidence: 99%
“…HypA (also known as HybF) is a Zn-containing protein (Atanassova and Zamble 2005)) but also binds stoichiometric amounts of nickel, and HypB is a GTPase (Blokesch et al 2004a;Leach et al 2005). The present model is that HypA serves as a nickel chaperone, and HypB as a regulator that thermodynamically controls the donation of the metal to the hydrogenase apoprotein or release of the nickel-free chaperone (Blokesch et al 2004c;Leach et al 2005;Reissmann et al 2003). The present model for HypA/HypB function (Leach et al 2005) involves a key metal binding site in HypB beyond the usual (Ni-binding) polyhistidine stretch.…”
Section: Accessory Proteins For Hydrogenase Maturationmentioning
confidence: 99%
“…In vitro analysis of H. pylori HypA revealed that it forms a homodimer that cooperatively binds two nickel ions and that the protein can associate with HypB (38). A Strep tag fusion of HybF from E. coli also binds nickel and/or zinc, but neither dimerization nor association with HypB was detected (7).…”
mentioning
confidence: 99%
“…SlyD can bind multiple nickel ions (23); however, the ⌬slyD strain of E. coli only has a partially deficient hydrogenase phenotype (54), suggesting that this protein is not the key nickel delivery factor. Instead, it has been proposed that HypA/HybF might serve as a source of nickel in E. coli and H. pylori at low metal concentrations (7,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HypA is a Ni-metallochaperone that binds to a Ni ion with micromolar affinity (17)(18)(19), and its structure consists of a Ni-binding domain (NiBD) and a Zn-binding domain (ZnBD) (20,21). The NiBD contains a highly conserved MHE motif that is essential for Ni binding at the N terminus (20,22).…”
mentioning
confidence: 99%